Phase field modeling of silicon nanowire based lithium ion battery composite electrode. (20th December 2015) - Xie, Yuanyuan; Qiu, Ming; Gao, Xianfeng; Guan, Dongsheng; Yuan, Chris
Highlights: A phase field model is developed for silicon nanowires based electrode. Coupling effect among deformation, lithiation and stress evolution are established. Modeling predictions are consistent with the experimental and analytical results. Large local stress negatively affects electrode depth of lithiation and fast charging. Si nanowire structure significantly influences electrode local stress evolution. Abstract: A phase field model is developed to investigate the silicon nanowire behaviors in lithium-ion battery electrode during its lithiation process. The coupling effect among lithium ion diffusion/insertion process, structure deformation and local stress/strain evolution are established. Modeling demonstrates that such coupling effect can significantly influence electrochemical performance of silicon composite electrode. On a 2D silicon nanowire geometry, Cahn-Hilliard equation and Ginzberg-Landau equations are developed and solved by finite element method. The developed model has nearly the same prediction on volumetric expansion ratio of silicon NW in comparison with the published experimental observation and can capture the a − L i η S i / c − S i phase boundary during lithiation. Numerical results show that large local stress exists in the outer region of silicon NW and could negatively influence the fast charging performance of silicon composite electrode. Results also show that small lithium mobility can limit the lithiation depth of silicon electrode during the charging process, and can result in reduced charge capacity of silicon composite electrode. By simulating different silicon NW structures, it is found that silicon NW structure can significantly influence the local stress distribution and evolution in silicon composite electrode. It is also found that porous silicon NW has potential structure degradation around the core region during its lithiation process. These obtained results can provide insights into the dynamic process of silicon electrode degradation and can assist in developing applicable high performance silicon electrode for future lithium ion batteries.